Liberal Feminism Analysis Of Gender Inequality In Hanung Bramantyo's Hijab Film (Study Of Feminism) - Nufiratul Awaliyah, Fira (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
Film is a work of oral literature in the form of a film which has many audiences. One of the films that is the aim of this research is the film Hijab. In this study aims to reveal gender inequality and women's struggles in demanding justice. in the film Hijab by Hanung Bramantyo, presents a male character who restricts women's work and presents a female character in fighting for equality that women also have the right and freedom to choose. This is done to change the way men think about women. The forms of gender injustice and women's struggles in this film are viewed from liberal feminism. This study uses descriptive qualitative research to obtain information and an overview of women's struggles based on liberal feminism. The results of the research show that gender inequality towards women in this film is patriarchal and subservient culture. In the household, the struggle of female characters based on liberal feminism consists of freedom. The struggle of female characters in making choices to independently carry out work without the knowledge of their husbands, the restrictions imposed by men are part of demeaning women related to work.